Extreme premature with persistent left superior vena cava - Aboitiz-Rivera, Carlos Manuel (Oxf Med Case Reports, 2017)
Persistent left superior vena cava (PLSVC) is a congenital anomaly, that results when there is an absence of the normal regression of the left common precardinal vein during embryogenesis. Usually, this anomaly remains asymptomatic, however, when the PLSVC drains into the left atrium this could lead to a right-to-left shunt. Additionally, this can result in inadvertent delivery of air or thrombus into the systemic circulation with potential neurologic, cardiac and renal complications. In this article, we present a case of an extreme premature Mexican newborn in which the diagnosis was made after placement of a percutaneous central venues catheter.